Epidemiological profile of HIV co-infection and visceral leishmaniasis in the state of Alagoas, 2009 – 2019 (Research, Society and Development, 2020)
Objective: To qualify the epidemiological profile of HIV co-infection and visceral leishmaniasis in the state of Alagoas in the last 10 years. Methodology: This is a descriptive, retrospective and quantitative study of confirmed cases of visceral leishmaniasis due to HIV coinfection in the state of Alagoas from 2009 to 2019. The data used are secondary from the Information and Aggravates Notification System (SINAN) found through the Department of Informatics of the Single Health System (DATASUS). Results: In the last 10 years, 503 cases of Visceral Leishmaniasis (VL) have been reported in the state of Alagoas, of which 27 (5.37%) are co-infected by HIV. When analyzing the profile of confirmed cases of Leishmaniasis by HIV coinfection, it was found that 77.8% are male, the age range of 20 to 39 years prevailed with 63% of the reported cases. Conclusion: The results found in this study show that in Alagoas there was a prevalence of Leishmaniasis due to HIV coinfection in men of reproductive age and low schooling. In this sense, understanding the epidemiological dynamics of VL, HIV/AIDS and VL/HIV-AIDS co-infection becomes a priority the inclusion of health education offers due to the lack of information such as risk factors related to pathologies in order to avoid HIV-LV co-infection in the state of Alagoas. Therefore, the formulation of effective measures for the control of these pathologies that are so relevant for the public health and epidemiological service.